The Encouragement Process in Guidance : Its Effect on School Achievement and Attending Behavior - Hillman, Bill W.; Shields, Frank L. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article illustrates how a counselor in his teacher-consultation role was able to model in the classroom the use of encouragement methods to improve the achievement and attending behavior of a seventh grade student. The author describes the specific procedures which were used and provides data to evaluate the result. Several significant implications for school counselors are suggested.